Thai soft power: Moving forward in the right direction - Kaewanant, Wilaiporn; Sirisunhirun , Somboon (Journal of Language and Culture, 2024)
This study presents policy guidelines that apply the concept of soft power as a mechanism for a country to enhance its bargaining power at the international level and pursue economic goals. Many countries have leveraged soft power to gain favor within the international community, at both the regional and global levels. Factors that give rise to soft power such as music, film and literature can enable a country to more easily attract and persuade others through a positive national image. Given that soft power is a multifaceted concept, such may be accomplished using cultural appeal, liberal political ideologies and values, favorable foreign policy agendas, and ethical behavior on the world stage. In recognition of the great benefits that regional neighbors such as Japan and South Korea have gained from soft power, the current and previous Thai government administrations have advanced policies aimed at soft power promotion to achieve economic development goals. These policies emphasize cultural resources that have been identified as broadly appealing and are easily accessible to domestic and international consumers. Among the myriad benefits Thailand would stand to gain through the spreading culture around the world include greater internationalization, cultural awareness, and appreciation for democracy and human rights. As this study shows, success in this endeavor is contingent upon private sector cooperation. The role of the government is thus to foster creative ecology and to support public diplomacy through the conveyance of relevant information conductive to promoting a positive national image.